2018
DOI: 10.20452/pamw.4311
|View full text |Cite
|
Sign up to set email alerts
|

Occult cancer and thromboembolism: current epidemiology and its practical implication

Abstract: Venous thromboembolism (VTE) may be the first presentation of malignancy. Up to 10% of patients with unprovoked VTE are diagnosed with occult cancer within 1 year. Cancer patients with concomitant VTE have a worse outcome. While limited screening strategy (thorough medical history, physical examination, basic laboratory tests, and chest X‑ray) and extensive screening strategy (limited screening plus computed tomography scan of the abdomen/pelvis or 18F-fluorodeoxyglucose positron emission tomography-computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…79 Based on the current guidelines, about 80% of patients with AF and cancer had indica tions for chronic anticoagulation. 80 Of note, can cer is associated with an increased risk of bleed ing related to thrombocytopenia, metastases, kid ney and liver damage, vessel damage caused by a tumor infiltrating its wall, invasive procedures, and radiation therapy. 69 Regarding patients with cancer and AF, most data are from observational studies.…”
Section: Scoring Systems To Predict Bleeding In Atrial Fibrillationmentioning
confidence: 99%
“…79 Based on the current guidelines, about 80% of patients with AF and cancer had indica tions for chronic anticoagulation. 80 Of note, can cer is associated with an increased risk of bleed ing related to thrombocytopenia, metastases, kid ney and liver damage, vessel damage caused by a tumor infiltrating its wall, invasive procedures, and radiation therapy. 69 Regarding patients with cancer and AF, most data are from observational studies.…”
Section: Scoring Systems To Predict Bleeding In Atrial Fibrillationmentioning
confidence: 99%
“…65 Cancer patients make up to 20% of all individuals with newly diagnosed VTE. 66,67 It has been suggested that clot properties, including impaired fibrinolysis, can be useful in identifying VTE patients at risk of developing or detecting malignant diseases following a negative initial standard cancer screening at VTE diagnosis. During a long-term follow-up, malignancy was diagnosed in 6% of VTE patients, who had several fibrin-related abnormalities, including impaired fibrinolysis (þ25.5% CLT) measured after a mean 4month anticoagulation had been stopped.…”
Section: Fibrinolysis Following Vtementioning
confidence: 99%
“…79 Based on the current guidelines, about 80% of patients with AF and cancer had indications for chronic anticoagulation. 80 Of note, cancer is associated with an increased risk of bleeding related to thrombocytopenia, metastases, kidney and liver damage, vessel damage caused by a tumor infiltrating its wall, invasive procedures, and radiation therapy. 69 Regarding patients with cancer and AF, most data are from observational studies.…”
Section: Specific Atrial Fibrillation Patient Populations At Risk Of mentioning
confidence: 99%